TOWARD A GOLDEN STANDARD OF EDUCATION: CONSTRUCTING THE OUTSTANDING SCHOOL MODEL IN MUHAMMADIYAH INSTITUTIONS - Mumthaza, Silwana; Utomo, Dwi Priyo; Purwanti, Elly; Pantiwati, Yuni; Rahardjanto, Abdulkadir (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Variations in institutional quality indicate the absence of a coherent and standardized framework for defining school excellence. Muhammadiyah has extensive contribution schools in Indonesia. Offers an integrative Outstanding School Model of Muhammadiyah as a strategic framework for achieving a golden standard in future-oriented education. The novelty of this study lies in the integration of Islamic values and future competencies into a unified Outstanding School Model of Muhammadiyah, which is further aligned with a real-world school evaluation system to establish a standardized framework for educational excellence. This study employs a qualitative design-based approach by integrating systematic literature review and document analysis to develop an Outstanding School Model of Muhammadiyah. The findings reveal that, although the MFS instrument is structurally comprehensive, it remains conceptually fragmented. Through thematic and quantitative analysis, its components are reorganized into four core dimensions: academic excellence, Islamic character (Al-Islam and Kemuhammadiyahan), future skills, and institutional quality. The results also indicate an imbalance in indicator distribution, with a strong emphasis on institutional aspects and limited integration of future-oriented competencies. The transformation of an existing evaluation system into a coherent and integrative framework that aligns Islamic educational values with global competencies. Furthermore, the model is aligned with SDG 4 Quality Education, reinforcing its relevance within global educational discourse. This study contributes by providing a standardized reference for improving school quality and guiding the development of Muhammadiyah education toward a sustainable and future-ready paradigm.